Solidarity economy: a strategy in the construction of peace for people in the process of reincorporation in Catatumbo - Santiago - Nava, Yeiny Paola; Alba - Maldonado, José Manuel (Universidad Francisco de Paula Santander, 2022)
The article focuses on a description of the processes of founding cooperatives from the principles of solidarity economy, carried out by people in the process of reincorporation from Catatumbo, former combatants of the FARC-EP Front 33, as a bet on the construction of peace. in the region. The cooperatives aim to develop collective productive projects in different activities and be a benchmark in Catatumbo that lead to regional development. The article has a descriptive qualitative methodology with primary information collection and interviews with people in the process of reincorporation. As results, the creation of 6 cooperatives in the Catatumbo region can be evidenced, which at this moment begin to develop productive projects with the support of the Francisco de Paula Santander University and national and international organizations.